2017
DOI: 10.1016/j.mcn.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Tubulins and brain development – The origins of functional specification

Abstract: The development of the vertebrate central nervous system is reliant on a complex cascade of biological processes that include mitotic division, relocation of migrating neurons, and the extension of dendritic and axonal processes. Each of these cellular events requires the diverse functional repertoire of the microtubule cytoskeleton for the generation of forces, assembly of macromolecular complexes and transport of molecules and organelles. The tubulins are a multi-gene family that encode for the constituents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 100 publications
0
63
0
Order By: Relevance
“…He was treated with Phenobarbitone (10 mg twice a day) and Levetiracetam The tubulins are a family of proteins that make up the constituents of microtubules, which play key roles in processes such as cell proliferation, neuronal migration, and cortical laminar organization in the developing brain. The human genome includes seven αand eight β-tubulin genes which share~88% of sequence homology (Breuss, Leca, Gstrein, Hansen, & Keays, 2017). Pathogenic variants in genes such as TUBB1 and TUBA4A cause distinct pathologies, while those in others result in overlapping phenotypes.…”
Section: Funding Informationmentioning
confidence: 99%
“…He was treated with Phenobarbitone (10 mg twice a day) and Levetiracetam The tubulins are a family of proteins that make up the constituents of microtubules, which play key roles in processes such as cell proliferation, neuronal migration, and cortical laminar organization in the developing brain. The human genome includes seven αand eight β-tubulin genes which share~88% of sequence homology (Breuss, Leca, Gstrein, Hansen, & Keays, 2017). Pathogenic variants in genes such as TUBB1 and TUBA4A cause distinct pathologies, while those in others result in overlapping phenotypes.…”
Section: Funding Informationmentioning
confidence: 99%
“…Unlike α‐tubulin and β‐tubulin, γ‐tubulin is not incorporated in the microtubule lattice but localizes to the centrosome during interphase. Defective microtubule function has been shown to lead to insufficient proliferation and ultimately, microcephaly 12,13 . Microtubule nucleation precedes the formation of bipolar spindles and separation of chromosomes in mitosis, steps that are necessary for the progression of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] For example, the beta‐tubulin isotype (βTub85D) is required for meiosis and axoneme assembly in the Drosophila male germline, [ 16 ] while the beta‐tubulin isotype βVI (TUBB1) determines the final cell shape of platelets, [ 17 ] and the beta‐tubulin isotype βIII (TUBB3) yields neural migration in mice (reviewed in ref. [18]). While the molecular mechanisms of isotype‐specific regulation of microtubule function is not fully understood, in vitro studies with purified recombinant tubulin demonstrated isotype specific polymerization dynamics.…”
Section: Microtubule Structure and The “Tubulin Code”mentioning
confidence: 99%